2013
DOI: 10.1039/c3cp53271b
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the dynamics and morphology of P3HT:PCBM active layers in bulk heterojunctions

Abstract: Organic photovoltaics (OPVs) are a topic of extensive research because of their potential application in solar cells. Recent work has led to the development of a coarse-grained model for studying poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) blends using molecular simulations. Here we provide further validation of the force field and use it to study the thermal annealing process of P3HT:PCBM blends. A key finding of our study is that, in contrast to a previous report, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 67 publications
8
74
0
Order By: Relevance
“…30 Finally, the structure factors computed from the P3HT:PCBM CG model employed in the present study were once again in good agreement with small-angle neutron diffraction experiments. 25,31 Hence, the CG model employed in the present study is capable of reproducing important morphological aspects also observed experimentally. In the following, we will briefly describe the CG models for the anode material (Al) and cathode material (PEDOT:PSS).…”
Section: Simulation Detailsmentioning
confidence: 79%
See 1 more Smart Citation
“…30 Finally, the structure factors computed from the P3HT:PCBM CG model employed in the present study were once again in good agreement with small-angle neutron diffraction experiments. 25,31 Hence, the CG model employed in the present study is capable of reproducing important morphological aspects also observed experimentally. In the following, we will briefly describe the CG models for the anode material (Al) and cathode material (PEDOT:PSS).…”
Section: Simulation Detailsmentioning
confidence: 79%
“…23 Recently, several CG models of P3HT:fullerene system have been developed for studying BHJ morphology evolution with system size compatible with experiments. 25,26 In addition to deterministic MD simulations, stochastic Monte Carlo (MC) is another powerful method to investigate the BHJ morphology at/close to equilibrium in solution, 27,28 which could hold the key toward studying longterm morphology evolution. However, all of these aforementioned computational studies focused on the BHJ morphologies in the bulk; that is, the top and bottom electrodes were not taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…A striking example of the diminishing simulation timescales accessible in large simulations is apparent in the 2013 work of Carrillo et. al., which used the then-fastest GPU-accelerated supercomputer in the world (Titan) to simulate evolving morphology in P3HT:PCBM active layers [38]. Simulating nearly 4 million particles, this work accessed the 100nm length-scales needed to model the full height of an active layer and accessed 400ns of simulation time, a significant achievement in scientific computing.…”
Section: Length Vs Time Trade-offmentioning
confidence: 99%
“…Accurate coarse-grained force fields require the potentials of mean force to be thoughtfully calculated from more detailed simulations if the coarse models are to be predictive over broad regions of state space [50,[52][53][54]. Alternatively, qualitative coarse-grained potentials permit the properties of a material system to be probed in response to assumptions about the underlying physics [38][39][40][55][56][57].…”
Section: Large-scale Morphology Predictionsmentioning
confidence: 99%
“…An extension of a recent large-scale coarse-grained molecular dynamics of P3HT/PCBM blend [15] indicates that the addition of low molecular weight P3HT polymer chains, as a third component of the blend, can be used to alter the morphology. Intuitively it is expected that shorter chains should be more mobile hence the system kinetics should be accelerated and equilibrium morphology is attained at a faster rate.…”
Section: Organic Photovoltaic Moleculesmentioning
confidence: 98%